Fantastyka naukowa w polskim piśmiennictwie krytycznofilmowym przełomu lat pięćdziesiątych i sześćdziesiątych XX wieku - Dudziński, Robert (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article is devoted to the Polish reception of science-fiction cinema; the statements of film critics from 1956–1965 were analysed. During this period, science fiction, previously absent from the screens of Polish cinemas for ideological and censorship reasons, returned to the repertoire and became the subject of press discussions and reviews. The analysis of articles devoted to this genre and published at the time allows reconstruction of the cultural context in which science-fiction productions operated. The article consists of three main parts. In the first of these, the author describes which science fiction films were present in Polish cinemas at the turn of the 1950s and 1960s. In the second part, he analyses press statements devoted to the history and aesthetics of the genre. The subject under consideration in the third part is the reception of two productions, which at the time enjoyed the greatest interest from contemporary critics: Godzilla (Gojira, 1954, dir. Ishirō Honda) and The Silent Star (Der schweigende Stern 1960, dir. Kurt Maetzig).